Razporeditve hiperravnin - Konvalinka, Matjaž (Obzornik za matematiko in fiziko, 2012)
A hyperplane arrangement is a finite set of hyperplanes (affine subspace of codimension 1) in the Euclidean space ?${\mathbb{R}}^n$?. In this surwey we define two basic structures: the intersection poset and the characteristic polynomial. We see how to use the characteristic polynomial to compute the number of regions created by the hyperplanes, and show some methods for finding the characteristic polynomial.
Keywords: arrangement; characteristic polynomial; delno urejena množica presekov; discrete geometry; diskretna geometrija; hiperravnina; hyperplane; intersection poset; karakteristični polinom; metoda končnih obsegov; razporeditev